Rigas modes. - Auzina, Ieva; Bankovskis, Pauls; Demakova, Helèna; Keita; Suvajevs, Igors; Timofeev, Sergey; Traumane, Mara; Rode, Emils; Weiland, Simona (Riga : Cultural Pilot Projects Riga, 2003)
Riga Fashion. Winter
Because pensioner fashion by definition does not change from year to year, this catalogue will not be a one-season product, but will remain topical for a long time. The title of Winter is, in a way, an ironic comment on the popular assumption that being a pensioner means being in the "winter" of life.
Catalogue published by Cultural Pilot Projects
Project by the creative group pureculture.
Riga Fashion. Winter
The aim of the project is to draw attention to the senior citizens of Riga as full-fledged, albeit subdued and unnoticed members of society; to encourage society to think about and discuss the fashion and styles peculiar to Riga, as well as about the aesthetics of old things as opposed to the corporate, industrial, developed capitalism one season fashion in clothing or any other aspect of life.
The first Riga Fashion catalogue is intended to be both a self contained publication featuring a photo collection and the current thinking in Latvia about pensioners, as well as a means of presenting the project at various events.
Keywords: Pureculture; Rozenfelds, Gatis